Inosperma subsphaerosporum (Inocybaceae), a new species from Hainan, tropical China - Deng, Lun-Sha; Yu, Wen-Jie; Zeng, Nian-Kai; Liu, Li-Jie; Liu, Li-Yue; Fan, Yu-Guang (Phytotaxa, 2021)
Inosperma subsphaerosporum sp. nov. is described from Hainan Province of China, based on morphological features and molecular phylogeny. The new species is characterized by a medium-sized basidioma, a scaly-fibrillose to rimulose pileus, subglobose to globose basidiospores, and thin-walled cheilocystidia. Moreover, I. subsphaerosporum is phylogenetically placed in an Old World tropical clade, in which all members described are from South Asia. Detailed descriptions, color photographs as well as comparisons between the new species and its closely related species are provided.